PERAN ILMU NAHWU DAN SHARAF DALAM PEMBELAJARAN BAHASA ARAB KONTEMPORER - Akbar, Aydil; Muhammad Syafi; Ahmad Zidan Al Faruqi; Delingga Nugraha; Fiqi Refianda Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Arabic language plays a strategic role in Islamic education because it serves as the source language of Islamic teachings. Proficiency in Arabic requires an understanding of linguistic rules, particularly the disciplines of Nahwu and Sharaf. However, in contemporary Arabic language instruction, these two disciplines are often perceived as difficult and lacking in practical application. This article aims to examine the role of Nahwu and Sharaf in contemporary Arabic language learning and their relevance to the needs of today’s students. This study employs a literature review approach, utilizing books on Nahwu and Sharaf as well as relevant scientific journal articles as data sources. Data were collected through documentation and analyzed using content analysis. The results indicate that Nahwu and Sharaf play a fundamental role as the foundation for understanding Arabic language structure, improving reading and writing skills, and serving as tools to aid in Arabic language learning. Furthermore, adapting the teaching of Nahwu and Sharaf to be contextual and practical is key to ensuring these disciplines remain relevant in contemporary Arabic language education. Thus, the integration of Nahwu and Sharaf into Arabic language instruction should aim for a balance between mastery of grammatical rules and functional language skills.